Hypersensitivity reactions to antiepileptic drugs in children. Issue 5 (20th May 2019) - Atanasković‐Marković, Marina; Janković, Jelena; Tmušić, Vladimir; Gavrović‐Jankulović, Marija; Ćirković Veličković, Tanja; Nikolić, Dimitrije; Škorić, Dejan
Abstract: Background: Antiepileptic drugs (AEDs) can cause hypersensitivity reactions in children. These reactions are mainly cutaneous, self‐limiting, and benign, but life‐threatening severe cutaneous adverse reactions can occur. Infections can lead to skin eruptions and mimic drug hypersensitivity reactions, if a drug is taken at the same time. The aims of our study were to confirm or rule out the diagnosis of hypersensitivity reactions to AEDs in children and to detect an infection which mimics these reactions. Methods: A prospective survey was conducted in a group of 100 children with histories of hypersensitivity reactions to AEDs by performing patch tests, delayed‐reading intradermal test, and, in case of negative results, challenge test. In all children, a study was performed to detect infections by viruses or Mycoplasma pneumoniae . Results: Maculopapular exanthema and delayed‐appearing urticaria were the most reported hypersensitivity reactions to AEDs. Sixty‐six (66%) of 100 children had confirmed hypersensitivity reactions to AEDs. Fifty‐nine children had positive patch test. No children had positive challenge tests. The most common AEDs causing hypersensitivity reactions were carbamazepine (45.4%) and lamotrigine (43.6%). Thirty‐two children had positive tests for viruses or M pneumoniae, and nine of them had also a positive allergy work‐up. Conclusion: Considering that there are no specific tests to distinguish between a viral infection and hypersensitivity reactions to AEDs in the acute phase, a diagnostic work‐up should be performed in all children with suspected hypersensitivity reactions to AEDs, as well as infectious agent study, to remove a false label of hypersensitivity.